2021
DOI: 10.3390/nu13113795
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Respiratory Infections in Infants with Cow’s Milk Allergy: An Expert Opinion on the Available Evidence and Recommendations for Future Research

Abstract: Acute respiratory infections are a common cause of morbidity in infants and young children. This high rate of respiratory infections in early life has a major impact on healthcare resources and antibiotic use, with the associated risk of increasing antibiotic resistance, changes in intestinal microbiota composition and activity and, consequently, on the future health of children. An international group of clinicians and researchers working in infant nutrition and cow’s milk allergy (CMA) met to review the avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Nevertheless, the clinical finding may also occur by coincidence given the chance of non immune related skin manifestations and the high prevalence of symptoms in the respiratory tract in childhood. Nevertheless, almost 70% of children with CMA report upper respiratory tract infections [19,20]. Sorensen et al found a higher prevalence of otitis media (25 vs. 19%; <0.01; rate 0.51 vs. 0.36; <0.01) and respiratory tract infections (89% vs. 82%; rate 6.88 vs. 5.03 (<0.01) and asthma (7.1 vs. 3.8%;<0.01) [13].…”
Section: A Score As a Diagnostic Or Awareness Tool?mentioning
confidence: 99%
“…Nevertheless, the clinical finding may also occur by coincidence given the chance of non immune related skin manifestations and the high prevalence of symptoms in the respiratory tract in childhood. Nevertheless, almost 70% of children with CMA report upper respiratory tract infections [19,20]. Sorensen et al found a higher prevalence of otitis media (25 vs. 19%; <0.01; rate 0.51 vs. 0.36; <0.01) and respiratory tract infections (89% vs. 82%; rate 6.88 vs. 5.03 (<0.01) and asthma (7.1 vs. 3.8%;<0.01) [13].…”
Section: A Score As a Diagnostic Or Awareness Tool?mentioning
confidence: 99%
“…Skin and respiratory tract manifestations occur frequently in infants with CMA and when GI and/or general manifestations are combined with skin and/or respiratory tract manifestations, the presence of CMA is more likely. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent retrospective study revealed that in infants under the age of two, sensitization to β-lactoglobulin (a protein found in cow’s milk) was linked to a nearly four-fold greater risk of recurrent respiratory tract infections. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Infants with CMA may have an increased susceptibility to infections (116). According to expert opinion in a review paper, secondary outcomes of trials suggest a trend in decreasing frequency and severity of respiratory tract (mainly) and GI infections as well as in reducing antibiotic intake in infants with CMA on an elimination diet supplemented with prebiotics, probiotics and synbiotics (116). In a retrospective study, with non‐standardized definition of CMA, GI, skin, respiratory and ear infections were reported to affect significantly more children with CMA than those without, increasing by 74% ( P < 0.001), 20% ( P < 0.001), 9% ( P < 0.001) and 30% ( P < 0.001), respectively (117).…”
Section: Clinical Gastro‐intestinal Presentation Of Cmamentioning
confidence: 99%
“…The high rate of respiratory infections in early life has a major impact on health care resources and antibiotic use with the associated risk of increasing antibiotic resistance, changes in intestinal microbiota and, consequently, on the future health of children. Infants with CMA may have an increased susceptibility to infections (116). According to expert opinion in a review paper, secondary outcomes of trials suggest a trend in decreasing frequency and severity of respiratory tract (mainly) and GI infections as well as in reducing antibiotic intake in infants with CMA on an elimination diet supplemented with prebiotics, probiotics and synbiotics (116).…”
Section: Risk For Infectious Diseasementioning
confidence: 99%